A pedagogical approach to solar energy education - Ott, Aadu; Broman, Lars; Blum, Konrad (Solar Energy, 2018)
The aim in this paper is to upgrade experiences from traditional studies on solar energy education to include social, sociological and pedagogical aspects. This is done in order to develop insights beyond production of artifacts. The aim is promotion of educational means for utilization of the artifacts developed. This includes upgrading knowledge about hardware as well as about software, and in this process also to upgrade our ways of thinking. This implies changing our neurological mindset in accordance with continuous development of knowledge within these domains. The scope of this paper is thus to discuss development of curricula and pedagogical means for teaching and learning within the domain of renewable energy education. The paper also aims to make a tentative approach to include solar energy education within the framework of an upgraded version of the socio-cultural theory for learning. A tentative approach is also made, with the intention, to connect this educational domain to educational neuroscience and to contemporary research on creativity.
Keywords: 21th century competences; Curriculum development; Educational neuroscience and creativity; Innovative learning environment; North Sun’88; Renewable energy education; Science education; Solar energy